Paradox theory and the paradox of success - Cunha, Miguel Pina e (2019)
Funding: FCT-Fundacao para a Ciencia e Tecnologia (grant nr. UID/ECO/00124/2013) and POR Lisboa (grant nr. LISBOA-01-0145-FEDER-007722)